A human-centric approach to artificial intelligence: ethical, social and economic challenges - Mancini, Riccardo; Pellegrini, Sara; Sebastiani, Riccardo; Glori, Debora (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The article explores a human-centric approach to artificial intelligence (AI), examining its ethical, pedagogical, and social implications through the perceptions of TFA students. The objective is to define guidelines for a sustainable and responsible use of AI that integrates fundamental values, promotes educational and social well- being, and critically addresses the challenges posed by automation.